(untitled) (FABICIB, 2025)
Food should be a right for the population. Food insecurity is a global problem, centred on access to food, affecting people in conditions of social vulnerability and poverty. This situation has an impact on the eating habits constructed and experienced. This work was born from our participation in "La Funda", an association that carries out its activities in the Southwest of Santa Fe, accompanying vulnerable children and their family groups through a comprehensive and transdisciplinary approach. The purpose of this research was to describe the physical, social and economic access to food and eating habits experienced by vulnerable families. We conducted interviews with the people responsible for food in the household, including: social, economic and demographic aspects; physical, social and economic access to food and eating habits. Vulnerable families have less access to resources and opportunities, as well as more disadvantages. They are recipients of social benefits, spend more than half of their income on food and live "day to day". Their diet is characterised by monotonous, few meals a day, fried foods and stews, poor in fresh foods and critical nutrients, excess of cereals and derivatives.